Evaluation of Caulerpa lentillifera as artificial feed on growth rate and survival level of carp (Cyprinus carpio)] - Erni Padu Lemba; Firat Meiyasa; Nurbety Tarigan (BERITA BIOLOGI, 2022)
This study aimed to evaluate the dose and utilization of Caulerpa lentilifera seaweed as artificial feed on the growth rate and survival rate of carp. This study used a completely randomized design (CRD) with four treatment levels and three replications. The fish used was carp (Cyprinus carpio) measuring 3-5 cm with a stocking density of 10 acres/bucket for 42 days of rearing. The doses of Caulerpa lentilifera flour added to the feed were 0%, 10%, 20%, and 30%. The results showed that the addition of Caulerpa lentilifera flour had a significant effect on growth rate, survival rate, feed utilization efficiency, and carp protein efficiency ratio. Giving Caulerpa lentilifera flour with a dose of 20% in the feed was the best dose for the relative growth rate of 6.83%, survival rate of 75%, efficiency of feed utilization of 20.59% and protein efficiency ratio of 3.79%. Caulerpa lentilifera in feed is able to increase the efficiency of feed utilization so as to support the growth rate and survival rate of carp